Homeostatic Regulation of ROS-Triggered Hippo-Yki Pathway via Autophagic Clearance of Ref(2)P/p62 in the Drosophila Intestine. - Nagai, H.; Tatara, H.; Tanaka-Furuhashi, K.; Kurata, S.; Yano, T. (Developmental Cell, 2021)
Homeostasis of intestinal epithelia is maintained by coordination of the proper rate of regeneration by stem cell division with the rate of cell loss. Regeneration of host epithelia is normally quiescent upon colonization of commensal bacteria; however, the epithelia often develop dysplasia in a context-dependent manner, the cause and underlying mechanism of which remain unclear. Here, we show that in Drosophila intestine, autophagy lowers the sensitivity of differentiated enterocytes to reactive oxygen species (ROS) that are produced in response to commensal bacteria. We find that autophagy deficiency provokes ROS-dependent excessive regeneration and subsequent epithelial dysplasia and barrier dysfunction. Mechanistically, autophagic substrate Ref(2)P/p62, which co-localizes and physically interacts with Dachs, a Hippo signaling regulator, accumulates upon autophagy deficiency and thus inactivates Hippo signaling, resulting in stem cell over-proliferation non-cell autonomously. Our findings uncover a mechanism whereby suppression of undesirable regeneration by autophagy maintains long-term homeostasis of intestinal epithelia.